MANTLE MIXING: THE GENERATION, PRESERVATION AND DESTRUCTION OF CHEMICAL HETEROGENEITY - van Keken P.E.; Hauri E.H.; Ballentine C.J. (My University, 2002)
Observations of the geochemical diversity of mid-oceanic ridge and ocean-island basalts have traditionally been attributed to the existence of large-scale mantle heterogeneity. In particular, the layered convection model has provided an important conceptual basis for discussing the chemical evolution of the Earth. In this model, a long-term boundary is assumed between a well-mixed and depleted upper mantle and a heterogeneous and more primitive lower mantle. The existence of high 3 He/ 4 He in ocean-island sources has been used to argue for the preservation of a primitive component in the deep mantle. Nevertheless, a primitive deep layer is difficult to reconcile with the abundant lithophile isotopic evidence for recycling of oceanic crust and the lack of preservation of primitive mantle. In addition, the widespread acceptance of geophysical evidence for whole mantle flow has made straightforward application of the layered convection model problematic. Model calculations show that whole mantle convection with present day heat flow and surface velocities is sufficiently vigorous to mix large-scale heterogeneity to an extent that is incompatible with the geochemical observations. Several concepts have been proposed in recent years to resolve the apparent conflicts between the various observational constraints and theoretical interpretations. The suggestions include the presence of deeper layering, preservation of highly viscous blobs, core mantle interaction, and strong temporal variations in mantle dynamics. Although these models generally appear to solve parts of the puzzle, at present no single model is able to account for all of the major observations. The reconciliation of conflicting evidence awaits improvements in observational and experimental techniques integrated with better model testing of hypotheses for the generation and destruction of mantle heterogeneity.